2021
DOI: 10.1177/20587384211036823
|View full text |Cite
|
Sign up to set email alerts
|

Essential amino acid supplementation is associated with reduced serum C-reactive protein levels and improved circulating lymphocytes in post-acute inflamed elderly patients

Abstract: Background Persistent systemic inflammation leads to multidistrectual body dysfunctions. Attenuation of inflammation may improve patients’ functional and life prognoses. We hypothesized that essential amino acids (EAAs) given to elderly patients in rehabilitation after acute diseases may be associated with a reduced inflammatory state. Therefore, this retrospective study investigated whether the supplementation of EAAs – modulators of immune competence – was associated with a reduced inflammation rate in elder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Others have also reported that the supplementation of EAAs reduced the inflammation rate in elderly patients. [ 61 ] In addition, dietary supplements of EAAs or whey proteins may also help in better functioning of the gut microflora which might improve health span and quality of life for older individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Others have also reported that the supplementation of EAAs reduced the inflammation rate in elderly patients. [ 61 ] In addition, dietary supplements of EAAs or whey proteins may also help in better functioning of the gut microflora which might improve health span and quality of life for older individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their effects on TJ structures, EAAs may reduce intestinal inflammation, as AAs may exert anti-inflammatory effects [ 33 , 35 , 56 ]. In elderly diabetic patients, supplemented EAAs decrease serum TNF α levels [ 34 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since TJ proteins have a fast turnover [ 31 , 32 ], they require adequate AA intake (in particular EAAs) in the intestinal lumen. Third, EAAs may exert an anti-inflammatory activity [ 33 , 34 , 35 ]. Fourth, in an experimental model of CKD (in mice), supplemented essential Branched-Chain AAs (BCAAs) have shown their capacity to re-equilibrate altered intestinal microbiota towards a development of healthier strains [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this fact explains the reduction of CRP levels when lysine and leucine were supplemented (79) and albumin regained its initial transport role.…”
Section: Albumin and Inflammatory Markersmentioning
confidence: 95%